Head-to-head comparison of pre-hospital qSOFA and lactate-qSOFA for predicting sepsis in patients with and without suspected infection. A multicenter prospective cohort study - Francisco Martín-Rodríguez; Raúl López-Izquierdo; Miguel A. Castro Villamor; Carlos delPozo-Vegas; Irene Sánchez-Soberón; Juan F. Delgado-Benito; Virginia Carbajosa Rodíguez; Rodrigues Leonardo; José Luis Martín-Conty (Archives of Medical Science)
Introduction The aim of the study was to compare the Quick Sequential Organ Failure Assessment tools (qSOFA), and Quick Sequential Organ Failure Assessment-Lactate (LqSOFA) to detect pre-hospital sepsis among patients with or without suspicion of infection.